Balneological clusters of Ukraine: scientific substantiation, standardization, development of treatment and resort areas - Gozhenko, Olena; Bykov, Igor; Kysylevska, Alona; Titov, Herman; Zukow, Walery (Journal of Education, Health and Sport, 2018)
The article presents an analysis of the existing normative methodological base of balneological resorts and the health potential of Ukraine. The strategic goal of development of tourist and resort industry of Ukraine is access to the world level of tourist and resort services. In this regard, work is underway to harmonize Ukrainian legislation and regulatory documents and European requirements in this area. The presence of natural medicinal resources, the state of infrastructure of sanatorium-resort institutions is the basic potential on the basis of which the attitude to recreational possibilities of resort territories is formed, that causes further Development of balneological clusters and the most sanatorium-and-spa sphere of Ukraine.